The chromosome region including the earliness per se locus Eps-Am1 affects the duration of early developmental phases and spikelet number in diploid wheat - Lewis, Silvina (2008)
Earliness per se genes are those that regulate flowering time independently of vernalization and photoperiod, and are important for the fine tuning of flowering time and for the wide adaptation of wheat to different environments. The earliness per se locus Eps-Am1 was recently mapped within a 0.8 cM interval on chromosome 1AmL of diploid wheat Triticum monococcum L., and it was shown that its effect was modulated by temperature. In this study, this precise mapping information was used to characterize the effect of the Eps-Am1 region on both duration of different developmental phases and spikelet number. Near isogenic lines (NILs) carrying the Eps-Am1-l allele from the cultivated accession DV92 had significantly longer vegetative and spike development phases (P <0.0001) than NILs carrying the Eps-Am1-e allele from the wild accession G3116. These differences were paralleled by a significant increase in the number of spikelets per spike, in both greenhouse and field experiments (P <0.0001). Significant interactions between temperature and Eps-Am1 alleles were detected for heading time (P <0.0001) but not for spikelet number (P=0.67). Experiments using NILs homozygous for chromosomes with recombination events within the 0.8 cM Eps-Am1 region showed that the differences in number of spikelets per spike were linked to the differences in heading time controlled by the Eps-Am1 locus. These results indicate that the differences in these two traits are either pleiotropic effects of a single gene or the effect of closely linked genes. A similar effect on spikelet number was detected in the distal region of chromosome 1AL in common wheat (T. aestivum L.).